2018
DOI: 10.1111/jfd.12907
|View full text |Cite
|
Sign up to set email alerts
|

Virulence regulation of cel‐EIIB protein mediated PTS system in Streptococcus agalactiae in Nile tilapia

Abstract: Streptococcus agalactiae is a major pathogen of tilapia causing significant economic losses for the global aquatic industry yearly. To elucidate the role of cel‐EIIB protein‐mediated phosphotransferase systems (PTS) in the virulence regulation of S. agalactiae, cel‐EIIB gene deletion in a virulent strain THN0901 was achieved by homologous recombination. The cellobiose utilization of △cel‐EIIB strain was significantly decreased relative to S.a.THN0901 strain incubating in LB with 10 mg/ml cellobiose (p < 0.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This is especially true for the first steps in the process concerning nutrient mobilisation and proliferation in the infected host. Several studies showed that the metabolism of glycans is an important factor for bacterial host colonisation (Chang et al, ; Koropatkin, Cameron, & Martens, ; Ng et al, ; Sonnenburg et al, ; Thomas et al, ; Xu et al, ). A global transcriptomic study conducted with E. faecalis revealed that during peritoneal infection of mice , 123 bacterial metabolic genes were differentially expressed (Muller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for the first steps in the process concerning nutrient mobilisation and proliferation in the infected host. Several studies showed that the metabolism of glycans is an important factor for bacterial host colonisation (Chang et al, ; Koropatkin, Cameron, & Martens, ; Ng et al, ; Sonnenburg et al, ; Thomas et al, ; Xu et al, ). A global transcriptomic study conducted with E. faecalis revealed that during peritoneal infection of mice , 123 bacterial metabolic genes were differentially expressed (Muller et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…After three washes with 1× PBS, serial dilutions of S. agalactiae were prepared. A total of 100 μL of serially diluted S. agalactiae were plated onto BHI plates for calculating the number of colony‐forming unit (CFU) (Xu et al., 2019). To determinate the LD50 (Laith et al., 2019), 50 Nile tilapia were divided into 5 groups, with 10 fish per group, and intra‐peritoneally injected with 0.1 ml of increasing concentrations of S. agalactiae (5 × 10 7 ; 1 × 10 8 ; 5.0 × 10 8 ; 1 × 10 9 ; 5 × 10 9 CFU/ml).…”
Section: Methodsmentioning
confidence: 99%
“…One study showed that there are different expression levels of the cel-PTS component cel-EIIB between low and high virulence GBS [ 55 , 56 ]. Xu et al (2018) reported that a cel-EIIB knockout strain showed a decreased ability of cellobiose utilization, as well as significantly reduced biofilm formation ability compared with the wild-type GBS strain [ 57 ]. It was also notable that knockout of cel-EIIB caused a 20% decrease in the accumulative mortality of tilapia due to GBS infection; the authors speculated that cel-EIIB knockout significantly decreased invasion and colonization efficiency [ 57 ].…”
Section: Virulence Factorsmentioning
confidence: 99%